2018
DOI: 10.1101/314989
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The metabolic redox regime ofPseudomonas putidatunes its evolvability towards novel xenobiotic substrates

Abstract: During evolution of biodegradation pathways for xenobiotic compounds, the transition towards novel substrates of Rieske non-heme iron oxygenases borne by environmental bacteria is frequently associated with faulty reactions. Such reactions release reactive oxygen species (ROS), endowed with high mutagenic potential. The present work studies how the operation of a given metabolic network by a bacterial host may either foster or curtail the still-evolving biochemical pathway for catabolism of 2,4-dinitrotoluene … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…These results are indicative of the biotransformation of 2,4‐DNT and, as reported previously, P . putida strains carrying the dnt gene cluster were not able to grow on 2,4‐DNT as the only carbon source (Akkaya et al , ). A separate quantitative analysis of the absorbance spectra of P. putida EM·DNT·S supernatants focused upon the first 8 h following 2,4‐DNT addition, revealing a characteristic absorbance rise at 420 nm (between 1‐4 h post‐inoculation).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are indicative of the biotransformation of 2,4‐DNT and, as reported previously, P . putida strains carrying the dnt gene cluster were not able to grow on 2,4‐DNT as the only carbon source (Akkaya et al , ). A separate quantitative analysis of the absorbance spectra of P. putida EM·DNT·S supernatants focused upon the first 8 h following 2,4‐DNT addition, revealing a characteristic absorbance rise at 420 nm (between 1‐4 h post‐inoculation).…”
Section: Resultsmentioning
confidence: 99%
“…We observed that the soluble fraction of 2,4‐DNT declined significantly within the first 4 h, and dropped to undetectable levels by 22 h. This kinetic pattern of 2,4‐DNT transformation is similar to what has been reported for Burkholderia sp. R34 (Pérez‐Pantoja et al , ) and other engineered P. putida strains (Akkaya et al , , ). Soluble levels of 2,4‐DNT declined in cultures of P. putida EM·S as well (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…arising from the native genomic and metabolic properties of the cells) or exogenous (i.e. due to the burden that producing a chemical compound at high yields usually imposes on the engineered cells) (Akkaya et al, 2018). Tackling this problem is therefore one of the major challenges in bringing bacterial chassis to actual industrial-scale bioproduction.…”
Section: Outlook and The Challenges Aheadmentioning
confidence: 99%
“…While the phenomenon that starts with ROS production brought about by deficient metabolization of DNT and ends with a high‐mutagenesis regime in B. cepacia R34 is well‐documented (Perez‐Pantoja et al, ; Akkaya et al, ), the molecular mechanisms behind the process are not clear. ROS can react directly with free or DNA‐bound nucleotides and generate variants (e.g., 8‐oxoguanine) that pair with the wrong partners in the helix and thus generate mutations.…”
Section: Introductionmentioning
confidence: 99%